Disqualification of Donor and Recipient Candidates From the Living Kidney Donation Program: Experience of a Single-Center in Germany - Grigorescu, Melissa; Kemmner, Stephan; Schönermarck, Ulf; Sajin, Isidora; Guenther, Wolfgang; Cerqueira, Tiago Lemos; Illigens, Ben; Siepmann, Timo; Meiser, Bruno; Guba, Markus; Fischereder, Michael; Johannes Stangl, Manfred (Frontiers in Medicine, 2022)
Background: Kidney transplantation is the best treatment option for patients with end-stage kidney disease (ESKD) with a superiority of graft survival after living kidney donation (LKD) compared to deceased donation. However, a large part of potential donors and recipients are ineligible for LKD. Here, we analyze the leading causes for disqualification of potential living donor-recipient pairs from the LKD program and the health-related consequences for ESKD patients excluded from the LKD program in a German transplant center. Methods: In this single-center retrospective cohort study we evaluated all candidates (potential donors and recipients) presenting for assessment of LKD from 2012 to 2020 at our transplant center. Thereby we focused on candidates excluded from the LKD program. Main reasons for disqualification were categorized as medical (donor-related), psychosocial, immunological, recipient-related and unknown. Results: Overall, 601 donor-recipient pairs were referred to our transplant center for LKD assessment during the observation time. Out of those, 326 (54.2%) discontinued the program with 52 (8.7%) dropouts and 274 (45.6%) donor-recipient pairs being ineligible for LKD. Donor-related medical contraindications were the main reason for disqualification (139 out of 274 (50.7%) potential donors) followed by recipient-related contraindications (60 out of 274 (21.9%) of potential donor-recipient pairs). Only 77 out of 257 (29.9%) potential recipients excluded from the LKD program received a kidney transplant afterwards with a median waiting time of 2 (IQR: 1.0 – 4.0) years. Overall, 18 (7.0%) ESKD patients initially declined for LKD died in this period. Conclusion: A large percentage of donor-recipient pairs are disqualified from the German LKD program, mostly due to medical reasons related to the donor and with partly severe consequences for the potential recipients. For these, alternative solutions that promptly enable kidney transplantation are essential for improving patient quality of life and survival.